Immunofluorescence in multiple tissues utilizing serum from a patient affected by systemic lupus erythematosus - Piotr Brzezinski; Michael S. Howard; Ana Maria Abreu Velez (Our Dermatology Online, 2012)
Introduction: Lupus erythematosus is a chronic, inflammatory autoimmune disease that can affect multiple organs. Lupus can affect many parts of the body, especially in systemic lupus erythematosus (SLE); affected tissues may include the joints, skin, kidneys, heart, lungs, blood vessels, and brain. Case report: A 46-year-old female presented with pruritus, photosensitivity and edema of the cheeks of about 2 years duration, and was evaluated by a dermatologist. On examination, multiple telangiectasias were present on the cheeks, with erythema, edema and a malar rash observed. A review of systems documented breathing difficulty and pleuitic pain, joint pain and joint edema, photosensitivity, cardiac dysrhythmia, and periodic pain in the back close to the kidneys. Methods: Skin biopsies for hematoxylin and eosin testing, as well for direct and indirect immunofluorescence were performed, in addition to multiple diagnostic blood tests, chest radiography and directed immunologic testing. Results: The blood testing showed elevated C-reactive protein. Direct and indirect immunofluorescence testing utilizing monkey esophagus, mouse and pig heart and kidney, normal human eyelid skin and veal brain demonstrated strong reactivity to several components of smooth muscle, nerves, blood vessels, skin basement membrane zone and sweat gland ducts and skin meibomian glands. Anti-endomysium antibodies were detected as well as others, especially using FITC conjugated Complement/C1q, FITC conjugated anti-human immunoglobulin IgG and FITC conjugated anti-human fibrinogen. Conclusions: We conclude that both direct and indirect immunofluorescence using several substrates can unveil previously undocumented autoantibodies in multiple organs in lupus erythematosus, and that these findings could be utilized to complement existing diagnostic testing for this disorder.